2021
DOI: 10.1021/acs.macromol.1c00513
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linking Effect on Segmental Dynamics of Well-Defined Epoxy Resins

Abstract: Epoxy resins with a network structure, which are obtained by curing reactions of epoxy and amine compounds, are an important class of thermosetting resins. We here report the segmental dynamics of epoxy resins in which the three-dimensional network was well-defined and systematically varied. What we found by experiments in conjunction with atomistic molecular dynamics simulation was that when the cross-linking density in the epoxy resins increased, the glass transition temperature increased with an associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 56 publications
3
57
0
Order By: Relevance
“…However, such an effect is not as clear as compared with the effect of the increased conversion degree as presented in Figure . We may also expect impacts of the HNS architecture on other important macroscopic properties of epoxy networks, such as fragility, thermal transition and degradation, moisture absorption, and solvent crack resistance, ,, which is the subject of our current research.…”
Section: Resultsmentioning
confidence: 99%
“…However, such an effect is not as clear as compared with the effect of the increased conversion degree as presented in Figure . We may also expect impacts of the HNS architecture on other important macroscopic properties of epoxy networks, such as fragility, thermal transition and degradation, moisture absorption, and solvent crack resistance, ,, which is the subject of our current research.…”
Section: Resultsmentioning
confidence: 99%
“…Epoxy resins, which are based on formation of networks between epoxy and amine compounds via curing reactions, are an important class of thermoset resins. Since epoxy resins are generally in a glassy state under ambient conditions, 1,2 epoxy resins are usually brittle, which is a critical drawback in resins used as structural materials. 3,4 One common approach to overcoming this issue is to disperse soft particles into the epoxy matrix as a filler.…”
mentioning
confidence: 99%
“…DGEBA and n -alkyl diamines were well mixed at a molar ratio of 2:1, which was equivalent in the stoichiometry of epoxy and amino groups to initiate the curing reaction. The mixture, which was heated up to 353 K, was placed on a Teflon substrate with a silicon mold and then pre-cured at 353 K for 12 h. All samples were further post-cured at 453 K for 12 h, resulting in an apparent completion of the reactions, which was confirmed by Fourier transform infrared (FT-IR) spectroscopy . Pre- and post-curing processes were conducted under a nitrogen atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…We recently studied the segmental dynamics of epoxy resins in which the three-dimensional network was well defined and systematically varied in terms of the cross-linking density . It was found that as the cross-linking density increased, the glass transition temperature ( T g ) increased with an associated reduction in the spatial size scale of the cooperative rearranging region (CRR).…”
Section: Introductionmentioning
confidence: 99%